Can health forums dedicated to breast cancer be useful to caregivers? Analysis of initial messages on the National League Against Cancer forum over a one-year period - Burgué, Hélène; Trensz, Philippe; Mathelin, Carole; Schohn, Anna (Gynécologie, obstétrique, fertilité & sénologie, 2024)
Forums are a source of health information and exchange. They can be studied to determine patients' needs and improve caregivers' practices. The aim of this study was to identify the needs of breast cancer patients based on messages posted on a discussion forum. Initial messages posted in 2021 on the Ligue nationale contre le cancer (LNCC) breast cancer forum were analyzed quantitatively. Message content was classified into three categories: testimonial, request for advice or request for medical opinion. The tone of the message (positive, neutral, or negative) was recorded. The temporality of the illness during which the patient expressed herself was defined. Analysis was carried out on the initial messages using the Chi , Fisher, and Kruskal-Wallis tests, with a significance level of<0.05. In 2021, 640 initial messages posted on the LNCC forum dedicated to breast cancer were analyzed. Messages were posted by 312 authors, including 275 patients and 37 family members. Three main types of messages were identified: requests for medical advice (n=339), advice (n=164), and testimonials (n=137). Requests for medical advice elicited fewer responses than testimonials (P<0.001). A need for supportive care was identified in 42.8% of messages, mostly concerning social (17.3%) and psychological (13%) care. Our study revealed a need for more information especially regarding the social impact of the disease and the side-effects of treatment. The period of greatest need of information was the diagnostic waiting time. However, patients using discussion forums are not representative of all women with breast cancer and our results should not be generalized to all patients treated for breast cancer.